Surface electrocoating of single carbon fibre with electroactive 3,4-ethylenedioxythiophene/1-p(tolylsulphonyl) pyrrole copolymer: effect of dielectric constant of solvent - Huner, Keziban; Sarac, A. Sezai (INDIAN ACAD SCIENCES, 2021)
In this study, we demonstrate the effect of dielectric constant of solvents on the electrochemical coating of poly(3,4-ethylenedioxythiophene) (PEDOT) and copolymer of 1-(p-tolylsulphonyl) pyrrole (pTSP) with 3,4-ethylenedioxythiophene (EDOT) as electroactive thin film on single carbon fibre microelectrodes in different dielectric constant media. The highest specific and double layer capacitance value was obtained with homopolymer (C-sp = 417 mF cm(-2), C-dl = 140 mF cm(-2)) and copolymer (C-sp = 218 mF cm(-2), C-dl = 67 mF cm(-2)) synthesized in dielectric constant of 64.9. As the dielectric constant decreased, both polymer and copolymer capacitance values were decreased. PEDOT has preserved more capacitive behaviour especially at lower frequency than poly(EDOT-co-pTSP). The effect of dielectric constant of solvent on the polymerization was examined by cyclic voltammetry (CV), equivalent circuit modelling (ECM) technique and electrochemical impedance spectroscopy (EIS). The surface properties of homopolymer and copolymer were inspected by using scanning electron microscopy (SEM), energy dispersive X-ray (EDX) point analysis.
Keywords: Electrodeposition; surface modification; thin film growth; ELECTROCHEMICAL IMPEDANCE SPECTROSCOPY; HIGH-PERFORMANCE; POLY(3,4-ETHYLENEDIOXYTHIOPHENE); MORPHOLOGY; POLYMERS; FILMS; ELECTROPOLYMERIZATION; SUPERCAPACITOR; TOLYLSULFONYL; CONDUCTIVITY; Materials Science